SISTEM PAKAR PENYAKIT KUDA (STUDI KASUS PEGASING ACEH TENGAH) - Ira Zulfa; Richa Septima; Hendri Syahputra (Pusat Riset dan Inovasi Nasional, 2022)
Disease is one of the factors that reduce the population of horses in Indonesia, in general, disease is a health problem. (T et al., 2015) In terms of origin, diseases can be grouped into two categories, namely diseases caused by infection and diseases caused by non-infection. Non-infectious diseases are diseases caused by the state of the body itself, such as allergies. and hormonal imbalance. The analytical method in this study uses the Certainty Factor (CF) method with several stages, namely data collection, problem identification, system design, system analysis, system implementation, and testing. Forward chaining reasoning technique which begins with the process of data collection and diagnostic facts. (Khoirul et al., 2021) forward chaining is carried out by using existing facts to draw conclusions, each fact will produce a conclusion in the form of a diagnosis and the process of indicating a measure of certainty against a fact or rule. The results of the study found that the results of collecting disease data, symptoms and rule bases obtained from an expert, can be made a disease rule chart, several symptoms of one type of disease and several symptoms with several diseases. Targeted outputs: Compulsory outputs are Monograph Books with ISBN with the title Application of Certainty Factor to detect racehorse disease (Case Study: Central Aceh Regency) and additional outputs of the Sinta 3 Accredited National journal.